2015
DOI: 10.1007/s00009-015-0634-z
|View full text |Cite
|
Sign up to set email alerts
|

Wiener Algebra for the Quaternions

Abstract: Abstract. We define and study the counterpart of the Wiener algebra in the quaternionic setting, both for the discrete and continuous case. We prove a Wiener-Lévy type theorem and a factorization theorem. We give applications to Toeplitz and Wiener-Hopf operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…We begin with the scalar-valued case. The following definition is analogous to the one for the discrete Wiener algebra (see [1]).…”
Section: An Almost Periodic Extension Of the Quaternionic Wiener Algebramentioning
confidence: 99%
See 3 more Smart Citations
“…We begin with the scalar-valued case. The following definition is analogous to the one for the discrete Wiener algebra (see [1]).…”
Section: An Almost Periodic Extension Of the Quaternionic Wiener Algebramentioning
confidence: 99%
“…In [1] it was shown that the discrete and continuous Wiener algebras are real Banach algebras. Along the same lines, we have: is countable, so we may enumerate it as (w m ) m∈N .…”
Section: An Almost Periodic Extension Of the Quaternionic Wiener Algebramentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, such a series does converge if the sequence of coefficients {a n } belongs to ℓ 2 (Z, H). Power series with coefficients in ℓ 1 (Z, H) are considered in [4]. Let L s (∂B) denote the space of measurable slice functions and, for 1 ≤ p < +∞, let L p (∂B) denote the space of (equivalence classes of) functions f : ∂B → H such that f p p := ∂B |f | p dΣ < ∞.…”
Section: Introductionmentioning
confidence: 99%